Activation and desensitization of ionotropic glutamate receptors by selectively triggering pre-existing motions. (1st May 2019) - Krieger, James; Lee, Ji Young; Greger, Ingo H.; Bahar, Ivet
Graphical abstract: Highlights: Intrinsic motions reveal couplings between ionotropic glutamate receptor domains. Allosteric communication between domains selectively exploits pre-existing motions. Global dynamics facilitates activation, allosteric signaling and desensitization. Elastic network models efficiently elucidate the pre-existing dynamics of iGluRs. Abstract: Ionotropic glutamate receptors (iGluRs) are ligand-gated ion channels that are key players in synaptic transmission and plasticity. They are composed of four subunits, each containing four functional domains, the quaternary packing and collective structural dynamics of which are important determinants of their molecular mechanism of function. With the explosion of structural studies on different members of the family, including the structures of activated open channels, the mechanisms of action of these central signaling machines are now being elucidated. We review the current state of computational studies on two major members of the family, AMPA and NMDA receptors, with focus on molecular simulations and elastic network model analyses that have provided insights into the coupled movements of extracellular and transmembrane domains. We describe the newly emerging mechanisms of activation, allosteric signaling and desensitization, as mainly a selective triggering of pre-existing soft motions, as deduced from computational models and analyses that leverage structural data on intact AMPA and NMDA receptors in different states.